Reproductive health education at SMP Negeri 23 Pekanbaru - Magdalena Magdalena; Melly Melly; Elvina Asnaty; Erni Forwaty (Universitas Muhammadiyah Magelang, 2023)
Breast cancer is a malignancy originating from glandular cells, glandular ducts and supporting tissues of the breast, excluding breast skin. Adolescence is a period of transition (transition from children to adulthood). At this time, adolescents often face complex and difficult problems to overcome on their own. The purpose of this community service is to increase young women's knowledge about reproductive health and skills about SADARI examination at SMP Negeri 23 Pekanbaru. This program was carried out in several stages, namely the preparation stage, the implementation stage and the evaluation stage. The results of the activity showed that most of the participants had good knowledge of reproductive health (60%) and were able to perform SADARI examinations (90%).